Studi Literatur : Peranan Aktivitas Fisik Terhadap Peningkatan Kemampuan Otak dan Aspek Kognitif - Syafruddin, Muhammad Akbar; Irvan; Hasanuddin, M. Imran (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
The purpose of writing this article is to explore further the role of physical activity in improving brain function and cognitive aspects and to provide a detailed description of a neuroscientific perspective on how physical activity can contribute to cognitive function in particular. The method used in writing this article is a literature study approach. The sources of information in this article come from various articles on Google Scholar, Elsevier, and Researchgate, using the keywords physical education, physical activity, cognitive aspects, and brain abilities. The articles used as sources of information in this study are articles published between 2013 and 2023. The conclusion from this literature study is that involvement in various physical activities in everyday life can help humans improve brain performance abilities and also encourage improvements cognitive aspect. Keywords: Physical Education, Physical Activity, Increasing Brain ability, Cognitive